Equivocations of power: an investigation of the post-colonial crisis of identity in four winners of the CNA literary award - Van Straaten, Dina Elyza (University of the Free State, 2005)
This thesis aims to investigate the post-colonial crisis of identity in four winners of the CNA Literary Award. Identity is explored from a deconstructive perspective by examining the master/slave, white/black, male/female and parent/child dialectics so as to demonstrate the variability and indeterminacy of the sign and the subsequent destabilizing of hierarchical discourses of power. The examining of identity from a deconstructive angle not only lays bare the instability underpinning positions of power, but also exposes the problematic of identity as a shifting, unfixed and decentred phenomenon. The research is focused on probing the dialectic between subjugator and subjugated, the empowered and the disempowered in order to develop an understanding of how imbalances of power inform and impact on the formulation of identity within the post-colonial context. It questions the decidability implied by binary structuring and challenges precepts of absolutism and totalization imbedded in the discourses pertaining to power relations and power differentials.
Keywords: Literary prizes -- South Africa; CNA Literary Award; South African fiction (English); Dissertation (M.A. (English and Classical Languages))--University of the Free State, 2005